The Effect of 4-2 Training Using Two Touches on Passing Skills and Shooting Ability in Mandalika FC U-17 Football - Maulana Husairi (Yayasan Baru Haji Samsudin, 2024)
In football, one of the most dominant basic techniques used is passing. Passing in football aims to pass the ball to teammates in order to create space, so that players can score goals against the opponent's goal and can maintain the defense area for defenders. The purpose of this study was to determine the effect of the 4-2 training model using two touches on the passing and shooting skills of Mandalika FC U-17 football athletes. This study is a quasi experiment. The design used in this study is